Military Education Collaboration between Countries - Syabilarrasyad, Syabilarrasyad; Irianto, Jusuf; Suhariadi, Fendy (Devotion : Journal of Research and Community Service, 2023)
The Unitary State of the Republic of Indonesia in the international arena has an active free politics, attitudes and views related to Indonesian foreign policy such as Indonesian foreign policy often have differences in attitude with other countries in responding to international issues. The Ministry of Defense, which covers the three branches of the TNI, namely the Army, Navy and Air Force, is very concerned about Military Academy education abroad by providing scholarships to Military Academy cadets / cadets to attend Military Academy education abroad, one of which is in Japan. This paper aims to analyze the collaboration of military education between countries, especially in Japan. The method used is qualitative by means of field case studies. This paper argues that a one-stop policy is needed in sending cadets / cadets of the Indonesian National Army Academy to attend Military Academy education abroad, where the Ministry of Defense must be positioned as the only door in the formulation and implementation of Military education collaboration policies between countries where the three TNI Matras must submit and obey as well as synergy with the Ministry of Defense in Military Education Collaboration between countries.